Living Under Security Certificates: Experiences of Securitization of Detainees and their Families - Wadhawan, Subhah (Université d'Ottawa / University of Ottawa, 2018)
Security and race have historically been entangled in the politics of nation-building, whereby national security discourses have constructed the ‘public’ whom it should protect as ‘white’ while demonizing persons of colour as a threat to that public. In the current war against terrorism, these racialized discourses, underwritten by a colonial logic, have materialized through the symbolic and literal displacement of Muslim persons. Under this imperative of national security, both existing and novel legislations have either been suspended, contorted, or implemented to be used against Muslims, or anyone who visibly appears Muslim. Security certificates are one of such judicial tools. This thesis seeks to explore the experiences of securitization, analyzing how this legislation strips the subjects of the security certificate program of their legal rights and social connectedness. To explore this, I interviewed three of the five men from the ‘Secret Trial Five’ cases and some of their family members. I investigate how securitization manifests in the lives of those who have been securitized, exploring the practices that are used to maintain and reinforce the othering and the displacement of Muslim populations.
Keywords: Security Certificates; Families; Secret Trial 5; Chinese Head Tax; Japanese Internment; Canadian National Identity; Lived experiences; National Belonging; Colonial State; Colonization; Qualitative interviews; Social Death; Civil Death; State of Exception; Securitization; Racialization; War on terror; Experiencs of Muslims within Canada; Experiences of Families of Incarcerated Persons; Exclusion; Othering; Moral indifference; Mohamed Harkat; Adil Charkoui; Hassan Almrei; Mahmoud Jaballah; Mohamed Zeki Mahjoub; House; surveillance; Body; Relationships